Direct structural evidence of Indian continental subduction beneath Myanmar - Tianyu Zheng (Nature Portfolio, 2020)
Indian continental subduction can explain crustal deformation, magmatic activity and uplift of the Tibetan Plateau following collision, however, the nature of the Indian subducting slab beneath Myanmar and the related tectonic regime remain unclear. Here, the authors present direct structural evidence of present-day Indian continental subduction beneath Asia.